A statistical quality control study on Anglo Watsons Glass, Incorporated - Laluces, Micheline L.; Tansionsgco, Gem Francesca V.; Utanes, Noel Nino (Quezon City College of Engineering, University of the Philippines Diliman, 2006)
Anglo Watsons Glass, Incorporated, is a subsidiary of Alliance Global Group, Inc. The company manufactures a variety of glass containers for the food and beverage industry. The group decided to focus on the inspection and quality control of the 700 ml glass container used for liquor, particularly the Generoso brand, more specifically the variables bore diameter, neck diameter, thread, height and body diameter. The specific objectives of this study include observing and documenting Anglo Watsons Glass Inc., generating control charts on critical quality characteristics of the product in focus, coming up with the process capability charts and evaluating the quality inspection activities of Anglo Watsons Glass, Inc. in its products, and ultimately, applying the skills learned in Statistical Quality Control. With the help of the Stream Diagnostic Chart, one major problem that was identified was the company's high percentage of rejects. Upon control charting, the processes deemed out of control were processes for the neck and bore diameter. Assignable causes for the out of control points were identified as the high furnace temperature causing breakage of molds, presence of residues in the molds, and the glass consistency being short of the desired thickness. Alternatives were then generated and evaluated. The top three given the highest ratings are recommended by the group. These are the use of control charts, tabulation of all factors that can affect output, and the use of Statistical Process Control software. These are recommended with cost in mind. If cost is not a setback for the company, the group also suggests replacement of the furnace. With the recommendations made, a decrease in the company's amount of rejects and increase in productivity is optimistically seen.
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial quality control.
Keywords: Glass containers; Quality control